Validation and Profile Modification of a Spur Gear to Improve the Gear Tooth Strengths (International Journal of Innovative Research in Computer Science & Technology, 2022)
The idea of using asymmetric tooth forms  has gained momentum in gearing design. Similar to  symmetric basic rack gears, tooth action parameters are  established in the first stage. The second stage involves  calculating the unified generating basic rack for a set of  mated gears. In some cases, it is possible to determine the  features of specific fundamental rack tooth profiles for each  gear in a transmission. Gearings with asymmetrical profiles  have the advantage of having a higher-pressure angle than  operational profiles (as a result of a lower pressure angle than  non-operating profiles) and the possibility for a considerable  improvement in the face contact ratio. In this study,  symmetric and asymmetric tooth profiles will be compared  using the finite element analysis tool Ansys. Asymmetric  (different pressure angle) and symmetric (different pressure  angle) tooth profiles will be designed and built in the 3D  modelling software CATIA. The designs made with different  materials will go through structural examination (mild steel  and EN 32 steel).
Keywords: Trochoid; Symmetric; Asymmetric; Inertia